How to Rewrite the History of Historiography? Prolegomena for a History of the Truth in History - Padilla, Guillermo Zermeño (História da Historiografia: International Journal of Theory and History of Historiography, 2015)
How to rewrite the history of historiography at the beginning of this century? This paper tries to answer this question using just four words: history, science, truth and credibility. The revision and transformation that has been done over the categories, concepts or ways of representing history, created during the nationalist modernity, leads us to question how is it possible to write history nowadays, since when those old contents and forms that settled historiographical commonplaces produced in the 19th and 20th centuries seem to have become exhausted. Therefore, we try to show how the crisis of a historical epistemology of “naturalistic” character gave rise to the possibility of considering historical discipline as part of a larger phenomenon: that of culture and its relationship to how societies remember or forget. At the same time, this displacement has also implied the construction of another class of social memory: the opening to the understanding of history as a kind of cultural memory.